Enhancing the Risk Management Functions in Banking: Capital Allocation and Banking Regulations - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
This chapter reviews capital allocation in the banking sector. Capital is crucial if banks are to be protected from banking risks. In order to ensure financial stability in the banking sector, banking regulators demand that banks hold sufficient capital to support their risks. The Basel Capital Accords, which aim to enhance the risk management functions of banks and to strengthen the stability of the international banking system, have introduced a common regulation framework for the capital allocation. They are international guidelines to encourage convergence toward common standards in the banking sector. The Basel Capital Accords have evolved over time because of the growth of international risks.